Enhancement of ZnO@RuO2 bifunctional photo-electro catalytic activity toward water splitting - Aleksić, Katarina; Stojković Simatović, Ivana; Stanković, Ana; Veselinović, Ljiljana; Stojadinović, Stevan; Rac, Vladislav; Radmilović, Nadežda; Rajić, Vladimir; Škapin, Srečo Davor; Mančić, Lidija; Marković, Smilja (Frontiers in Chemistry, 2023)
The catalytic materials are the greatest challenge for the commercial application of water electrolyzes (WEs) and fuel cells (FCs) as clean energy technologies. It is necessary to find an alternative for expensive and unavailable platinum group metal (PGM) catalysts. The aim of this research was to reduce the cost of PGM materials by replacing Ru with RuO2 and to lower the amount of RuO2 by adding abundant and multifunctional ZnO. ZnO@RuO2 composite in 10:1 molar ratio was synthesized by microwave processing of a precipitate as green, low-cost and fast method, and then annealed at 300 and 600 oC to enhance catalytic properties. The physicochemical properties of the ZnO@RuO2 composites were studied by X-ray powder diffraction (XRD), Raman and Fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM), UV-Vis diffuse reflectance (DRS) and photoluminescence (PL) spectroscopy. The electrochemical activity of the samples was investigated by linear sweep voltammetry in both acidic and alkaline electrolytes. We found good bifunctional catalytic activity of the ZnO@RuO2 composites toward HER and OER in both electrolytes. The enhanced bifunctional catalytic activity of the ZnO@RuO2 composite by annealing was discussed and attributed to reduced concentration of the bulk oxygen vacancies.